2019
DOI: 10.1001/jama.2019.5118
|View full text |Cite
|
Sign up to set email alerts
|

Penalties and Rewards for Safety Net vs Non–Safety Net Hospitals in the First 2 Years of the Comprehensive Care for Joint Replacement Model

Abstract: Role of the Funder/Sponsor: The funders had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Compared with results from our main analysis, findings were qualitatively similar overall in analyses using models with hospital-clustered standard errors and without hospital fixed effects (Appendix Figures 10,11…”
Section: Sensitivity Analysissupporting
confidence: 66%
See 1 more Smart Citation
“…Compared with results from our main analysis, findings were qualitatively similar overall in analyses using models with hospital-clustered standard errors and without hospital fixed effects (Appendix Figures 10,11…”
Section: Sensitivity Analysissupporting
confidence: 66%
“…[4][5][6][7][8] In the context of bundled payments for joint replacement surgery, safety net hospitals have been less likely to achieve financial savings but more likely to receive penalties. [9][10][11] Moreover, the savings achieved by safety net hospitals have been smaller than those achieved by non-safety net hospitals. 12 Despite these concerning findings, there are few data about how safety net hospitals have fared under bundled payments for common medical conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Reinforcing this concern, other studies have found that hospitals serving high proportions of low-income patients under CJR were penalized more than other hospitals. 27 , 32 In contrast, our study suggests that despite CJR’s unfavorable design toward hospitals serving high proportions of low-income patients, CJR-participating hospitals may have been able to improve care for Black, but not Hispanic, patients: Black patients’ readmissions decreased despite reductions in their institutional postacute care use.…”
Section: Discussionmentioning
confidence: 57%
“… 9 , 10 , 46 , 47 This rationale for unfavorable selection is further supported by concerns that the investments made in quality improvement in preparation for payment reforms and the resulting capabilities may motivate hospitals to increase their case volumes with perceived healthier patients, thereby leaving out beneficiaries from racial/ethnic minority groups and increasing the existing disparities. 5 Furthermore, the absence of having to consider sociodemographic risk adjustment places an increased burden on safety net hospitals, 48 , 49 , 50 and these hospitals may be particularly cautious in selecting socially vulnerable patients for surgical procedures. Potential explanations for CJR model–associated disparities in TKRs and not in THRs are likely to be a greater need for institutional rehabilitation after TKRs, especially for beneficiaries from racial/ethnic minority groups, 51 , 52 higher adverse events, 53 and longer recovery.…”
Section: Discussionmentioning
confidence: 99%